Learn OpenOffice.org spreadsheet macro programming OOoBasic and Calc automation : a fast and friendly tutorial to writing macros and spreadsheet applications - Bain, Mark Alexander; Safari eBooks (Birmingham, U.K. : Packt Pub., 2006)
"This book teaches the OOoBasic language and the Calc object model, so that you can manipulate spreadsheets and data from within your programs. You will also see how to create dialog boxes and windows for friendly user interfaces, and how to integrate your spreadsheets with other applications, for example writing spreadsheet data to a document, or capturing data from a database, and using the spreadsheet for generating advanced calculations and reports"--Resource description page.
Description based on print version record.
Includes index.
Keywords: OpenOffice.org (Electronic resource); Arithmetic -- Data processing; Business -- Computer programs; Electronic spreadsheets -- Computer programs; Electronic books